2022
DOI: 10.1002/ctm2.902
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory roles of external cholesterol in human airway epithelial mitochondrial function through STARD3 signalling

Abstract: Background Hypercholesterolemia is found in patients with chronic lung inflammation, during which airway epithelial cells play important roles in maintenance of inflammatory responses to pathogens. The present study aims at molecular mechanisms by which cholesterol changes airway epithelial sensitivity in response to smoking. Methods Human bronchial epithelial cells (HBEs) were stimulated with cigarette smoke extract (CSE) and mice were exposed to CS/lipopolysaccharide (LPS) as models in vitro and in vivo. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 73 publications
(156 reference statements)
1
28
0
Order By: Relevance
“…Even with second-hand smoke, HDL cholesterol levels are lower in dyslipidemic children [ 26 ]. A recent publication demonstrated elevated plasma levels of cholesterol in COPD patients [ 27 ]. The exact mechanisms for how smoking affects the lipid profile are not understood but are postulated to be related to catecholamine release with subsequent changes in circulating free fatty acids and resultant increases in VLDL and LDL with a decrease in HDL [ 28 ].…”
Section: Is There a Relationship Between Smoking Status And Lung Chol...mentioning
confidence: 99%
See 3 more Smart Citations
“…Even with second-hand smoke, HDL cholesterol levels are lower in dyslipidemic children [ 26 ]. A recent publication demonstrated elevated plasma levels of cholesterol in COPD patients [ 27 ]. The exact mechanisms for how smoking affects the lipid profile are not understood but are postulated to be related to catecholamine release with subsequent changes in circulating free fatty acids and resultant increases in VLDL and LDL with a decrease in HDL [ 28 ].…”
Section: Is There a Relationship Between Smoking Status And Lung Chol...mentioning
confidence: 99%
“…Recently, Li et al demonstrated that immune responses in airway epithelial cells are also influenced by cholesterol [ 27 ]. They observed that cigarette smoke extract (CSE)-induced expression of IL8 and IL6 in human bronchial epithelial (HBE) cells could be reversed by either a statin (atorvastatin) or LXR agonists (T0901317 and GW3965) [ 27 ].…”
Section: Cholesterol Levels Can Influence Systemic and Local Lung Inf...mentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous data demonstrated that exogenous cholesterol supplementation altered the transcriptomic profiles of CS‐stimulated bronchial epithelial cells and cholesterol homeostasis, as well as ribosome and mitochondrial function (Figure 4). 102 STARD3‐mediated mitochondrial cholesterol overload initiates mitochondrial dysfunction, including membrane potential, respiration, dynamics and morphology. The imbalance in mitochondrial dynamics altered lipid homeostasis in lung epithelial cells, probably contributing to the exacerbation of inflammation in COPD.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%